PERAN GENDER DALAM SERIAL NOVEL THE TWILIGHT SAGA KARYA STEPHANIE MEYER: SEBUAH KAJIAN FEMINIS (Gender Role in Stephanie Meyer’s Novel Series The Twilight Saga: a Feminist Criticsm) - Marliza , Edria Yeni, Sandika (SALINGKA, 2014)
Literary works are often chosen by feminists as a medium to promote gender equality between men and women. Many women writers portray their female characters as intelligent and independent women and give them equal gender role with the male characters. This article applies feminist approach to analyze the construction of gender role in The Twilight Saga series (2005-2008) written by Stephanie Meyer to see how Meyer, as a woman writer, constructs gender role through her main characters of the novel series. The writers apply Helene Cixous’s theory of patriarchal binary thought which dichotomizes man and woman as two different poles. The analysis shows that the series of four novels represent a hierarchical dichotomous gender role: man is described as subject and centre while woman is the object and margin. Such gender role is evidently a decline in the long struggle of gender equality that has been fought by many women